PENGARUH KERAGAMAN PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA CAFE AYAH BUNDA DI KABUPATEN SITUBONDO ABDURACHMAN SALEH SITUBONDO - Firdausia, Rini (Fakultas Ekonomi dan Bisnis, 2023)
This study is to determine the effects of product diversity, price, and service quality on consumer satisfaction at Cafe Ayah Bunda in Situbondo. The data analysis methods used in this research are validity test, reliability test, classical assumption test, multiple linear regression analysis, t-test, f-test, dominant test, and coefficient of determination. The results of multiple linear regression indicate that the variable product diversity (X1), price (X2), and service quality (X3) have a positive influence on the variable visitor satisfaction (Y). This is shown in the results of multiple linear regression analysis Y = 2.550E-16 + 0.671X1 -0.226X2 + 0.121X3+ e. The value for the product diversity variable is t-count 7,320 > t-table 1,985 has a partial effect on consumer satisfaction. Price variable -tcount -2.454 > ttable 1.985 has a partially negative effect on consumer satisfaction. The service quality variable t-count 1.472 < t-table 1.985 has no partial effect on consumer satisfaction at Cafe Ayah Bunda in Situbondo. The f-test shows the calculated f-value of 20.107 > 2.70, so it can be concluded that the research hypothesis (H2) which states that the variables of product diversity, price, and service quality have a simultaneous effect on consumer satisfaction. Based on the dominant test, the value of the product diversity variable is greater than the other variables by 7,320.